HIV prevention and care services for female sex workers: efficacy of a targeted community‐based intervention in Burkina Faso. Issue 1 (14th September 2015) - Traore, Isidore T; Meda, Nicolas; Hema, Noelie M; Ouedraogo, Djeneba; Some, Felicien; Some, Roselyne; Niessougou, Josiane; Sanon, Anselme; Konate, Issouf; Van De Perre, Philippe; Mayaud, Philippe; Nagot, Nicolas
Abstract : Introduction: Although interventions to control HIV among high‐risk groups such as female sex workers (FSW) are highly recommended in Africa, the contents and efficacy of these interventions are unclear. We therefore designed a comprehensive dedicated intervention targeting young FSW and assessed its impact on HIV incidence in Burkina Faso. Methods: Between September 2009 and September 2011 we conducted a prospective, interventional cohort study of FSW aged 18 to 25 years in Ouagadougou, with quarterly follow‐up for a maximum of 21 months. The intervention combined prevention and care within the same setting, consisting of peer‐led education sessions, psychological support, sexually transmitted infections and HIV care, general routine health care and reproductive health services. At each visit, behavioural characteristics were collected and HIV, HSV‐2 and pregnancy were tested. We compared the cohort HIV incidence with a modelled expected incidence in the study population in the absence of intervention, using data collected at the same time from FSW clients. Results: The 321 HIV‐uninfected FSW enrolled in the cohort completed 409 person‐years of follow‐up. No participant seroconverted for HIV during the study (0/409 person‐years), whereas the expected modelled number of HIV infections were 5.05/409 person‐years (95% CI, 5.01–5.08) or 1.23 infections per 100 person‐years ( p =0.005). This null incidence was related to a reduction in the number of regular partners and regular clients, and by an increase in consistent condom use with casual clients (adjusted odds ratio (aOR)=2.19; 95% CI, 1.16–4.14, p =0.01) and with regular clients (aOR=2.18; 95% CI, 1.26–3.76, p =0.005). Conclusions: Combining peer‐based prevention and care within the same setting markedly reduced the HIV incidence among young FSW in Burkina Faso, through reduced risky behaviours.